Sublethal effects associated with resistance to indoxacarb in diamondback moth - Rodríguez-Rodríguez, José Francisco; Cerna-Chávez, Ernesto; Ochoa-Fuentes, Yisa María; González-Figueroa, Sarahyt Santamaría; Guevara-Acevedo, Luis Patricio; Cisneros-López, Hugo Cesar (Ecosistemas y Recursos Agropecuarios, 2024)
Plutella xylostella is one of the most important pests of brassicaceous crops around the world. Indoxacarb is widely used to control lepidopteran pest larvae. This insecticide has slow activity and prolonged residual effects which impact the habits and physiology of pests. The objective was to evaluate the effect of sublethal concentrations of indoxacarb on the biology and development time of the diamondback moth. Selection pressure of the insecticide indoxacarb was carried out on P. xylostella, applying the LC20 of the previous generation for the next ten generations, the LC20 of the resistant line (G10) was calculated and this concentration was subsequently applied to L3 larvae. The effect on the percentage and weight of pupae, adult emergence and oviposition for two generations was evaluated; in addition, the development time of egg, larva, pupa and adult. The results showed that resistance and exposure to LC20 of indoxacarb caused changes in the biology and development of P. xyllostella. This was manifested in an increase in the percentage and weight of formed pupae and emergence of adults, along with a prolongation of development time of more than 10 days. However, a decrease of more than 50% in the number of eggs per female was observed.
Keywords: Insecticide; Biology; Transgenerational; Plutella xylostella